The magnesium isotope (δ26Mg) signature of dolomites. (15th January 2015) - Geske, A.; Goldstein, R.H.; Mavromatis, V.; Richter, D.K.; Buhl, D.; Kluge, T.; John, C.M.; Immenhauser, A.
Abstract: Dolomite precipitation models and kinetics are debated and complicated due to the complex and temporally fluctuating fluid chemistry and different diagenetic environments. Using well-established isotope systems (δ 18 O, δ 13 C, 87 Sr/ 86 Sr), fluid inclusions and elemental data, as well as a detailed sedimentological and petrographic data set, we established the precipitation environment and subsequent diagenetic pathways of a series of Proterozoic to Pleistocene syn-depositional marine evaporative (sabkha) dolomites, syn-depositional non-marine evaporative (lacustrine and palustrine) dolomites, altered marine ("mixing zone") dolomites and late diagenetic hydrothermal dolomites. These data form the prerequisite for a systematic investigation of dolomite magnesium isotope ratios (δ 26 Mgdol ). Dolomite δ 26 Mg ratios documented here range, from −2.49‰ to −0.45‰ (δ 26 Mgmean  = −1.75 ± 1.08‰, n  = 42). The isotopically most depleted end member is represented by earliest diagenetic marine evaporative sabkha dolomites (−2.11 ± 0.54‰ 2σ, n  = 14). In comparing ancient compositions to modern ones, some of the variation is probably due to alteration. Altered marine (−1.41 ± 0.64‰ 2σ, n  = 4), and earliest diagenetic lacustrine and palustrine dolomites (−1.25 ± 0.86‰ 2σ, n  = 14) are less negative than sabkha dolomites but not distinct in composition. Various hydrothermal dolomites are characterized by a comparatively wide range of δ 26 Mg ratios, with values of −1.44 ± 1.33‰ (2σ, n  = 10). By using fluid inclusion data and clumped isotope thermometry (Δ47 ) to represent temperature of precipitation for hydrothermal dolomites, there is no correlation between fluid temperature (∼100 to 180 °C) and dolomite Mg isotope signature (R 2  = 0.14); nor is there a correlation between δ 26 Mgdol and δ 18 Odol . Magnesium-isotope values of different dolomite types are affected by a complex array of different Mg sources and sinks, dissolution/precipitation and non-equilibrium fractionation processes and overprinted during diagenetic resetting. Further progress on the use of δ 26 Mgdol as a proxy will require new theoretical and experimental data for Δ 26 Mgfluid-dol that includes dehydration effects of the free Mg aquo ion versus fluid temperature. In ancient diagenetic systems, complex variables must be considered. These include fluid chemistry and physical properties, Mg sources and sinks, temporal changes during precipitation and post-precipitation processes including open and closed system geochemical exchange with ambient fluids. All of these factors complicate the application of δ 26 Mgdol as proxy for their depositional or diagenetic environments. Nevertheless, the data shown here also indicate that δ 26 Mgdol can in principle be interpreted within a detailed framework of understanding.